Investigation of Pressure Relief Borehole Effects Using In Situ Testing Based on Distributed Optical Fibre Sensing Technology. (13th January 2021) - Li, Yunpeng; Sun, Dequan; Zhao, Shankun; Liang, Kaihua; Cui, Kai; Wang, Huaihong
Abstract : Borehole pressure relief method is one of the most effective ways of rock burst prevention in coal mines. The measured results of borehole pressure relief at no. 8939 longwall face in Xinzhouyao coal mine, China, are presented here. The analyses identify the pressure relief magnitudes in coal mass around the boreholes with different diameters, spacing, and drilling time. This research has established that the best pressure relief of the rib coal can be achieved by using φ 108 mm borehole with 0.7 m interval after 288 hours. The strain relief is acceptable after 288–360 hours of drilling, while the best result is achieved after 432 hours. It is also the first time to monitor the borehole pressure relief in a coal mine on-site using Brillouin optical time domain reflectometer (BOTDR) distributed fibre-optic sensing. The method implemented in this research provides new ways to improve stress relief design and minimize the rock burst occurrence for mine practitioners.